Do Social Connections and Digital Technologies Act as Social Cure During COVID-19? - Pandey, Vijyendra; Astha, Arora; Mishra, Neelam; Greeshma, Rajgopal; Lakshmana, Govindappa; Jeyavel, Sundaramoorthy; Rajkumar, Eslavath; Prabhu, G (Frontiers in Psychology, 2021)
Although COVID-19 pandemic has re-orientated humans to be more physically healthy and hygienic, it has also persuaded humans to create affiliations and experience a sense of belongingness through social networks and digital technologies. However, amidst these changes, experiences of COVID-19 patients and their perception of the outside world’s attitudes towards them appears to be less attended in literature which formed the basis for the current study’s objectives. Using qualitative methodology, the present study explored the experiences, perceptions and attitudes of patients and their care-givers’ towards COVID-19. The thematic analysis emerged with four major themes. Psychological Experiences of People was generated prominently with sub-themes indicating the perceived experiences like fear of spreading diseases to others, and the need for psychological counselling. Attitude of others toward patients and caregivers revealed that family members and relatives played a major positive role on the patient’s mental health, however, the neighbour’s stigmatized attitude led to several undesired behaviours. Social Connectedness was another major theme derived from the study. Altruistic volunteers, a sub-theme of Social connectedness have indicated that amidst these negative factors, one can spread social harmony by motivating and supporting the victims with basic needs, financial support, hope and social empathy. Opinions of participants for digital technology through technological aids and preventive measures emphasized an overall positive attitude as it helped the society, in general to maintain social connections as well to curb the rate of COVID-19 cases.